Teks Ucapan Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim Naib Canselor Universiti Malaysia Pahang Sempena Opening Ceremony of the International Conference on Automotive Innovation and Green Energy Vehicle 2016 - Pejabat, Naib Canselor UMP (Universiti Malaysia Pahang, 2016)
It is with great pleasure that I have the honour of welcoming all of you this morning, on this auspicious occasion that marks the commencement of the International Conference on Automotive Innovation and Green Energy Vehicle or AIGEV 2016. First and foremost, I would like to convey the warmest regards from the Vice-Chancellor of UMP, Yang Hormat Professor Dato’ Dr. Daing Nasir Ibrahim who is unable to be with us this morning and he has asked to represent him in welcoming you all today.